Analisis Tingkat Keamanan Enkripsi Data Menggunakan Algoritma Base 64 Endcode - Annas Apreja; Zulfadhli Syarif; Ali Ibrahim (Annual Research Seminar (ARS), 2017)
Abstract - In the digital era like nowadays, The information system is well developed. As an indicator can be seen advances in technology of the data security that are increasingly developed along with the needs of people with communication data. The Analysys Of Data Security Using Base64 Algorithm is an analyse about how well this level of security algorithm that often used by developer. As more developed the science is, also developed the Base64 Algorithm. Base64 is a method for encoding binary data to texts. The binary data is encoded to 7-bit character format. With this analyse we can know the data security level using Base64 algorithm.